(untitled) (Nigerian Journal of Health Sciences, 2023)
Background: HIV/AIDS Counseling and Testing (HCT) is an effective tool in HIV prevention and control. However, perceived hindrances may limit the utilization of HIV Counseling and Testing (HCT) services, particularly among high-risk groups. Therefore, this study assessed perceived hindrances and factors influencing the acceptability of (HCT) among commercial drivers. Methods: This was a cross-sectional survey of commercial drivers in Ife Central Local Government Area. Data were analyzed using Statistical Package for Social Sciences for Windows version 20. The dependent variable for the multiple regressions was commercial drivers willingness to uptake free HCT services in their motor parks, while independent variables were their age, marital status, and the level of education. Results: Three-hundred commercial drivers were surveyed. 76 (25.3%) of respondents had previously undergone HIV test. 184 (61.3%) of the 300 respondents were willing to uptake HCT services. Perceived possible hindrances to HCT uptake were fear of a positive HCT test by 259 (86.3%), stigmatization by 260 (86.7%), lack of in‑depth knowledge about HCT 258 (86.0%), and confidentiality concerns by 267 (89.0%) while 151 (50.3%) perceived poor access to HIV testing services as a hindrance. Multivariate analysis revealed that drivers aged 30–39 years were twice more likely to accept HCT service compared to their 20–29-year-old colleagues. Car drivers were twice more likely to accept HCT compared to bus drivers, whereas drivers with secondary education were four times less likely to accept HCT compared with their colleagues with tertiary education. Conclusion: This study revealed that a high proportion of drivers was willing to uptake HCT services. The introduction of free HCT education and services at motor parks would, therefore, enhance HCT uptake